Risk management and internal control disclosure among Malaysian listed issuers / Raja Adzrin Raja Ahmad ... [et al.] - Raja Ahmad, Raja Adzrin; Zakaria, Nor Balkish; Mohamed Yunos, Rahimah; Ahmad, Syahrul Ahmar; Abdullah, Norhidayah (Universiti Teknologi MARA Cawangan Selangor, 2016)
Over the years, firms have been pressured by various stakeholders to be transparent about how they operate. In this regard, good corporate governance should ensure timely and accurate disclosure is made on a firm's financial, risk management and internal control. Hence, the purpose of this study is to construct an index for risk management and internal control. This index used to assess the extents of Malaysian listed firms' compliance of the risk management and internal control guidelines created for directors of listed issuers. The index was developed based on the requirements, under Paragraph 15.26(b) of Bursa Malaysia Securities Berhad's Main Market Listing Requirements ('Listing Requirements'), as guided by the 'Statement on Risk Management and Internal Control: Guidelines for Directors of Listed Issuers'. This guideline, which was released on 31 December 2012, incorporates the revision made to the Statement on Risk Management & Internal Control: Guidelines for Directors of Listed Issuers (issued in 2000). The findings of this study reveal that the compliance score by the sample firms reach about 70 per cent. The result is beneficial to the industry led Task Force to ascertain how the revised guidelines were incorporated into corporate governance dislosure. The findings of this study could also be useful for firms to determine the adequacy of their risk management and internal control practices and ensure that these guidelines are communicated appropriately and effectively. This, in turn, will assist firms to achieve their corporate objectives and match stakeholders' expectations within an ethical and healthy corporate culture.